ASSESSMENT OF ANTIBIOTIC SENSITIVITY PATTERN OF MICROORGANISMS, AND THEIR COST- EFFECTIVENESS AT A PRIVATE CORPORATE HOSPITAL IN SOUTH INDIA - Thomas, Bijoy; Matthew, Leo; Jose, Jerrin; Rathinavelu, Mohanraj; Shanmugam, Sriram; Kumar, K. Krishna (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objectives: Wide reports in the literature from different parts of the world revealed that antibiotics are used both widely and indiscriminately. Antibiotics are prescribed unnecessarily and empirically for complaints where no antibiotic is required or where culture and sensitivity results could be safely awaited. The current study was designed to assess the antibiotic sensitivity pattern of microorganisms and to analyze the antibiotic usage pattern and to conduct a cost-effectiveness analysis for the antibiotics prescribed. Methods: The retrospective study of 6 months duration was conducted in 500 bedded multi-specialty private corporate hospital of South India, including all the inpatients in the Department of General Medicine and Pulmonology for whom at least one antibiotic was prescribed. Results: In the sensitivity pattern study, a total of 796 documented records was analyzed and it was found that Escherichia coli was the major organism identified in 36.4% of the isolated specimens, followed by Klebsiella, Streptococcus pneumoniae, Staphylococcus aureus and Pseudomonas. The sensitivity pattern data revealed that E. coli were highly sensitive to Amikacin, followed by Klebsiella to amikacin, and Pseudomonas to meropenem. In the study, lower respiratory tract infection was found to be the most common disease in 51 patients. Cephalosporins (73%), in particular ceftriaxone (63.5%) was highly prescribed. ceftriaxone was found to be more cost-effective antibiotic in comparison to levofloxacin. Conclusion: The study concluded that pharmacist’s role in assisting prescribers on antibiotic prescribing is vital in achieving rational drug use and reducing resistance. Keywords: Antibiotics, Observational study, Prescribing pattern, Rational drug use, Cost effective analysis.